ANALISIS RUGI-RUGI DAYA KABEL DC PADA PLTS 1MWP ON-GRID INSTITUT TEKNOLOGI SUMATERA BERDASARKAN DATA FUSION SOLAR - Gde KM Atmajaya; Syamsyarief Baqaruzi; Bernardus Galih Dwi Wicaksono; Sabhan Kanatan; Ali Muhtar (Journal of Science, Technology, and Visual Culture, 2022)
PLTS 1 MWp on-grid at the Sumatra Institute of Technology (ITERA) campus comprises solar modules, inverters, DC cables, and protection equipments assembled in a compact system. Each of these components has a role in transmitting the electrical energy generated by the solar module to the electrical load at ITERA. This paper will discuss the power losses generated by PLTS components, especially the DC distribution cables used. The simulation of PVSystV6.81 obtained 1.98% of the losses resulting from the distribution process on the DC cable. The simulation results were compared with the measurement results from the solar fusion software, which records the power components generated by PLTS ITERA such as voltage, current, power, etc. for each string connected to the inverter with a data collection duration of 5 minutes (12 hours per day 06.00 – 18.00). Based on data obtained from fusion solar in August and formula calculation, the lowest average percentage loss of energy from DC cables is 0.6542% on inverter 6, and the highest is 0.6718% on inverter 1. The difference losses of each inverter are caused by disturbances in the DC cable distribution line from the module to each inverter, such as short circuit current to ground.